Marginal Utility of Money and Elasticities of Demand - Pigou, A. C.; Friedman, Milton; Georgescu-Roegen, N. (Quarterly Journal of Economics, 1936)
A. C. Pigou, Milton Friedman, N. Georgescu-Roegen; Marginal Utility of Money and Elasticities of Demand, The Quarterly Journal of Economics, Volume 50, Iss